Pemikiran Mohammad Nizarul Alim Tentang Akuntansi Syariah - Ansahrizal, Wahyu; Nurlaila, Nurlaila; Daim Harahap, Rahmat (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
This study aims to find out what Mohammad Nizarul Alim thinks about Sharia Accounting. This study uses a qualitative method with a descriptive approach, explaining the journey of his life and work. Data sourced from supporting literature related to research. In this study, it was found that Mohammad Nizarul Alim's thoughts on Sharia accounting that traces of Islam had contributed to the accounting trail long before Lucas Pacioli was known as the inventor of modern accounting. Sharia accounting is a manifestation of the effort to achieve material and spiritual welfare (Al-Falah) which is integrated between economic, social, and political originating from Islamic sharia. Islamic law has a goal for the welfare of all mankind, which lies in maintaining faith (din), self/human life (nafs), intelligence (aql), offspring (nasl), and wealth (mal).